Seismic behavior of frames with innovative energy dissipation systems (FUSEIS1-2). (1st May 2015) - Dimakogianni, Danai; Dougka, Georgia; Vayas, Ioannis
Highlights: Innovative FUSEIS1-2 seismic resistant system and design recommendations. Non-linear static analysis (SPO) – Evaluation of behavior factor. Self-centering – Capability of eliminating residual drifts after earthquake. Low cycle fatigue considerations – Determination of the damage index of the pins. IDA method: median curve, fragility curve, Adjusted Collapse Margin Ratio (ACMR) calculation. Abstract: Modern seismic codes allow for inelastic deformations in dissipative zones during design earthquakes, accepting damage to a certain extent in the relevant structural parts. In the frame of a European Research Program "FUSEIS" two innovative seismic resistant systems were introduced and relevant design guides developed. The first system, named FUSEIS1, consists of a pair of closely spaced strong columns joined together by a number of fuses. This system is further subdivided in FUSEIS1-1 where the dissipative fuses are beams and in FUSEIS1-2 where the fuses are short pins. This paper reports on the seismic performance of buildings with FUSEIS1-2 systems. It discusses results of nonlinear static and dynamic analyses that were based on element properties as derived by the tests and provides design recommendations and appropriate behavior factors. The results confirm the good seismic performance of the system under seismic loading and its capacity to develop self-centering properties under certain conditions.